2015
DOI: 10.1136/jech-2014-205368
|View full text |Cite
|
Sign up to set email alerts
|

First-borns have greater BMI and are more likely to be overweight or obese: a study of sibling pairs among 26 812 Swedish women

Abstract: Our study corroborates other large studies on men, and the steady reduction in family size may contribute to the observed increase in adult BMI worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 21 publications
2
17
0
1
Order By: Relevance
“…In addition, the Register does not record paternal anthropometric data, so that the possible associations between fathers’ and daughters’ BMI could not be investigated. Further, as this study only covered first-born daughters, future studies should assess whether a similar trend exist among later-born daughters, especially since we have recently shown that first-borns have greater BMI and increased odds of obesity compared to their second-born sisters in Sweden 22 . Lastly, there were very limited data on maternal birth parameters, so that we were unable to exclude mothers born preterm, from multiple births, or congenital malformations.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the Register does not record paternal anthropometric data, so that the possible associations between fathers’ and daughters’ BMI could not be investigated. Further, as this study only covered first-born daughters, future studies should assess whether a similar trend exist among later-born daughters, especially since we have recently shown that first-borns have greater BMI and increased odds of obesity compared to their second-born sisters in Sweden 22 . Lastly, there were very limited data on maternal birth parameters, so that we were unable to exclude mothers born preterm, from multiple births, or congenital malformations.…”
Section: Discussionmentioning
confidence: 98%
“…Anthropometric differences in adulthood were examined with generalized linear regression models. All adjusted models included the smoking habit of the woman's mother during pregnancy 31 , birth order 32,33 , and year of birth (to account for population-wide trends). Weight and BMI models also included current regular smoking (pre-pregnancy and/or during pregnancy) and age, while the "weight [ht adj]" model also adjusted for current height.…”
Section: Study Populationmentioning
confidence: 99%
“…However, birth order may also be of importance as lower birth order has been linked to higher BMI (19) , fat mass (12) , and overweight or obesity (20) .…”
mentioning
confidence: 99%